DEVELOPMENT OF BASIC KNOWLEDGE IN EDUCATIONAL ACTIVITY USING BASIC KNOWLEDGE IN TEACHING ORGANIC CHEMISTRY - A. T. Jurayev (International Engineering Journal For Research & Development, 2021)
The article discusses the issues of adjusting the basic knowledge of students as a necessary condition for obtaining a quality education.